Emergency Department Nurses' Clinical Competence and Its Related Factors: A cross-sectional study - Fatemeh Jalalian; Seyed Mohammad Hosseininejad; Seyed Hossein Montazer; Ali Hesamzadeh (ACHSM, 2023)
Objectives: This study aimed to assess perceived clinical competence levels of emergency department nurses in Iran and to identify association with the demographic variables. Methods: In this cross-sectional study, all 131 employed nurses from emergency departments of four educational hospitals were included in the study using a census method. Data collection tools included a demographic information form and the "Nurse Competence Scale". Data were analyzed using descriptive and analytical statistics. Results: The mean age of the nurses was 32.41± 6.35 years. 14 nurses were male and 117 nurses were female, the average work experience of the nurses was 8.48±5.98 years. The mean score of nurses' clinical competence score of the nurses was 68.68 ± 3.24 out of 100, which was a "good level". Among the subscales of clinical competence, the highest mean score was related to "managing situation" and lowest to "ensuring quality". There was no statistically significant difference of clinical competence by gender, age, and academic degree. However, the level of clinical competence differed significantly depending on work experience. Conclusions: The emergency department nurses at Mazandaran University of Medical Sciences, Iran, reported a good level of clinical competence across all categories. Hospital managers' awareness of the level clinical competence of emergency department nurses helps them design educational programs and effective training session to improve the quality of nursing services. Moreover, it is necessary to upgrade nursing education programs at all levels of nursing education in to improve graduating nurses' clinical competences.